Strategi Penguatan Peran Pelabuhan Murhum sebagai Hub Maritim di Wilayah Kepulauan Buton - Andi Tenri Andi; La Didi; Catur Suryo Mulyanto (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to analyze strategies to enhance the role of Murhum Port as a maritime hub in the Buton Archipelago region. The method used is a mixed-method approach with a sequential exploratory design, in which the research begins with qualitative methods and is subsequently complemented by quantitative methods. The analytical approach employed is SWOT analysis through the identification of internal factors (strengths and weaknesses) as well as external factors (opportunities and threats) that influence port development. The results of the study indicate that Murhum Port has several strengths, including its strategic geographical position on the regional sea distribution route, the support of local commodities, the involvement of third parties, and supportive government policies. However, there are still several weaknesses, particularly in bureaucratic processes, limited modern infrastructure, the need for improved logistics digitalization, and the integration of hinterland access. From the external perspective, opportunities such as strengthening national maritime connectivity, increasing inter-island trade, and the availability of alternative financing schemes serve as key driving factors. Nevertheless, these opportunities are accompanied by challenges, including budget efficiency constraints and dependence on central government policies. The SWOT analysis results show an S–W value of 0.04 and an O–T value of 0.21, placing the port in Quadrant I (progressive growth strategy). Therefore, the development strategy should focus on optimizing external opportunities through the simultaneous and sustainable strengthening of internal capacities to realize Murhum Port as a competitive regional maritime hub.